The association between underlying conditions, risk factors, risk markers, and post-COVID conditions ≥6 months after COVID-19: A systematic review - Aisha Hill; Madelon Morford; Sharon Saydah; Pamela Logan; Danielle Raso; Erin C. Stone; Joanna Taliano; Emilia H. Koumans; Olga Varechtchouk (Journal of Family Medicine and Primary Care)
Introduction: While various demographic factors and underlying medical conditions are associated with the development of post-COVID conditions within a month after SARS-CoV-2 infection, less is known about factors associated with post-COVID symptoms that persist for 6 months or more. The aim of this review was to determine the association between underlying conditions, other risk factors, health behaviors, and the presence of symptoms ≥6 months after COVID-19. Methods: Studies reporting on post-COVID symptoms were searched in databases, including Medline, EMBASE, Global Health, PsycInfo, Scopus, CINAHL, Proquest, and WHO COVID-19 literature, from the beginning of the pandemic until November 2022. Studies were included if they reported on symptoms ≥6 months after COVID-19 and a relevant measure of association (adjusted or unadjusted odds or risk ratio). Results: A total of 17 studies with 109,293 participants met the inclusion criteria; they were conducted in China (3), Italy (3), Spain (3), Russia (2), France (1), Germany (1), Sweden (1), Scotland (1), United Kingdom (1), and the United States (1). When compared to males, female participants were at an increased risk of post-COVID-19 symptoms (risk ratio (RR): 1.24; adjusted odds ratio (aOR): 3.08). Underlying conditions, including COPD/lung disease, overweight status or obesity, hypertension, cardiovascular disease, and asthma, were identified as possibly being associated with an increased risk of post-COVID symptoms. Conclusion: Female gender and certain underlying medical conditions were associated with an increased risk of post-COVID symptoms ≥6 months after COVID-19. Further research is needed to better understand some of these associations and identify groups that are at increased risk for persistent post-COVID conditions.